Pengaruh Dana Pihak Ketiga, Fee Based Income, Non Performing Financing, Financing to Deposit Ratio, Overhead Cost, terhadap Pembiayaan pada PT Bank Syariah Bukopin dengan Total Aset sebagai variabel Intervening - Ami Nullah Marlis Tanjung (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2018)
This research aims to determine and analyze the relationship among Total Assets on Financing, Third Party Funds on Financing and Total Assets, Non Performing Financing on Financing and Total Assets, Fee Based Income on Total Assets, Financing of Deposit Ratio on Financing, and Overhead Costs on Financing at PT Bank Syariah Bukopin for the 2010 - June 2018 research year.The technique of data collection in this study usedtime seriessecondary dataon the quarterly published financial statements of PT Bank Syariah Bukopin. The analytical method used Descriptive Analysis and Classical Assumption Test as well as Analysis path helped by LISREL Software version 8.8. Based on the results of the research conducted on alpha 5%, the researcher concluded that the results of calculating diagram of LISREL path analysis showed that the variables of Third Party Funds that had an effect on intervening variables were Total Asset, but Fee Based Income and Non Performing Financing took no effect on Total Assets. Then Third Community Funds and Financing of Deposit Ratio had a significant effect on Financing. However, Total Assets, Non Performing Financing, Overhead Costs had no effect on Financing at PT Bank Syariah Bukopin in the year of research.